Wechselwirkungen zwischen Klimaschutz- und Klimaanpassungsmaßnahmen in der Regionalplanung. - Säwert, Katja (My University, 2016)
Die Arbeit formuliert zwei Erkenntnisfelder. Das inhaltliche konzentriert sich auf die Erhebung von Wechselwirkungen zwischen regionalplanerischen Klimaschutz- und Klimaanpassungsmaßnahmen. Ausgehend von den zehn durch die Ministerkonferenz für Raumordnung (MRKO) für Klimaschutz und Klimaanpassung genannten Handlungsfelder erfolgt für jedes Handlungsfeld die Wahl einer Maßnahme. Die zugrunde liegende Annahme ist, dass eine Wechselwirkung sich durch eine Verschneidung der regionalen Bedeutung und des regionalen Einflusses einer Maßnahme ergibt. Um die Bedeutung und den Einfluss zu erheben, wird für das methodische Erkenntnisfeld ein Analyserahmen erstellt, bestehend aus Methodenkomponenten des Analytical Hierarchy Process (AHP) und der Sensitvitätsanalyse. Der AHP ermittelt einen Bedeutungskoeffizienten, der das Gewicht einer Maßnahme aus Sicht der Regionalplanung darstellt. Das Vorgehen ermöglicht es, die Maßnahmen entsprechend ihrer regionalen Relevanz in einer Rangfolge abzubilden. Anhand der Sensitivitätsanalyse werden folgend die gegenseitigen Einflüsse zwischen den Maßnahmen aufgezeigt. Die Bewertungen erlauben die Ableitung verschiedener Rollen, die den Maßnahmen eine aktive, reaktive, kritische oder puffernde Rolle zuweisen. Die Erhebung der empirischen Daten erfolgte mittels einer halbstandardisierten Befragung der regionalen Planungsstellen in Deutschland. Die Auswertung der Befragung bietet zum einen Erkenntnisse über die Wahrnehmung von Klimaanpassungs- und Klimaschutzmaßnahmen. Des Weiteren zeigt sie mögliche Konflikte und Synergien zwischen den zehn untersuchten Maßnahmen auf. Für jede Maßnahme wird ein Interaktionspotenzial definiert. Vor dem Hintergrund der Komplexitätstheorie werden die Ergebnisse abschließend erörtert. Die Ergebnisse aus der Erhebung münden in einer Reflexion des Rollen- und Steuerungsverständnisses der Regionalplanung. Demnach ergeben sich Wechselwirkungen zwischen den regionalplanerischen Maßnahmen nicht ausschließlich in Abhängigkeit vom Planungsobjekt, sondern gestalten sich ebenso vor dem Hintergrund des Planungssubjektes dar. Die Erkenntnisse dieser Arbeit werden anhand von fünf Kernaussagen zusammenfassend dargestellt.

Climate change has gained increasing attention in recent years. Both climate mitigation and climate adaptation have become more and more important in science as well as regional planning practice. Simultaneously, they pose new challenges for the regional planning practice. This includes for example considering climate change impacts on a supra-regional level, the resulting need for adaptation and dealing with uncertainties of climate predictions. Therefore, the German Adaption Strategy (DAS) emphasises the importance of regional planning in its function as a cross-sectoral planning institution and attributes high importance for a successful management of climate change challenges to it (Bundesregierung 2008, 42). Also research considers regional planning as a crucial level for coordination and decision-making, due to its region-oriented and supra-local perspective. Measures of both strategies - mitigation and adaptation - often are characterized by their supra-local implications (ARL 2009a, 9; Birkmann et al. 2010, 5, 19; Frommer 2009, 129; Schlipf, Herlitzius & Frommer 2008, 77). Given the current state of research two knowledge gaps were identified. Firstly, so far no analysis of possible interactions between climate mitigation and adaptation measures for the regional planning level in Germany has been conducted (BMVBS 2010a, 81). Secondly, no suitable methodological approach for characterising interactions between different measures could be identified in the existing literature. Based on these first insights two research areas were defined. The first one addresses the content, analysing possible interactions between mitigation and adaption measures for regional planning. Based on the ten actions fields for mitigation and adaptation determined by the conference of ministers for spatial planning (MKRO), one measure per field is chosen. The underlying assumption here is that an interaction is the result, intersecting regional importance and regional influence of a measure. The degree of importance and influence will be analysed within the developed coherent analytical framework. This framework combines methodical components from the Analytical Hierarchy Process (AHP) and the Sensitivity Analysis developed by Frederic Vester. The AHP determines a coefficient for the importance of measures based on a pairwise comparison. The value obtained constitutes the weighting of each measure, as a result of the assessment made by the interviewed regional planners. Using components of the AHP allows ranking the measures in relation to their regional importance. Components of the Sensitivity Analysis on the other hand enable identifying the reciprocal impact between measures. Based on a pairwise comparison of measures different roles will be derived, assigning each measure an active, passive, critical or buffering capacity. For collecting the empirical data, a semi-structured survey addressing regional planning institutions in Germany is used. The analysis of the survey provides insights into the planners perception of the importance of climate mitigation and adaptation measures on the one hand and on the other hand into the reciprocity between them. Thus possible conflicts and synergies among the ten evaluated measures can be determined. Based on the research outcome, for each measure an interaction potential will be defined. Finally the research results will be reflected against the background of complexity theory. The outcomes induce a critical reflection of the regional planner s self- and governance-perception. According to that, interactions between regional planning measures are not solely a result of measures and thus planning object, but are influenced additionally by the regional planning framework, thus the planning subject. Consequently, interactions are much more a qualitative result of the interplay between various regional factors. The thesis generates five key messages summarising the outcome of the research conducted.
Interrelationships between climate mitigation and adaptation at the regional planning level in Germany.
Keywords: Regionalplanung; Umweltschutz; Klima; Wirkungsanalyse; Planungsinstrument; Wahrnehmung; Befragung; Klimaschutz; Klimaanpassung; Klimaschutzmaßnahme; Anpassungsmaßnahme